Characteristics of fracture field in different stress zones during multi‐seam mining: Quantification based on theoretical analysis and BBM‐DEM accurate simulation method. Issue 5 (25th January 2020) - Cheng, Zhiheng; Ouyang, Zhenhua; Zou, Quanle; Lu, Yun; Zhao, Xidong; Li, Meichen
Abstract: The revelation of the distribution characteristics of stress and fractures in the floor strata is of great significance to improve the regional gas drainage efficiency and to eliminate or reduce the risk of coal and gas outburst in adjacent coal seams during multi‐seam mining. In this paper, the stress distribution in the floor under mining condition was derived, and the characteristics of stress zones in the floor were elaborated while mining the 22201 working face in Shaqu coal mine in Shanxi province, China. Besides, the propagation laws of fractures in different stress zones were theoretically analyzed, and the distribution law of fracture angles in the floor strata under different mining‐induced stresses was obtained. The research results demonstrate that the compression and transition zones show high vertical stress and less developed fractures and are dominated by fractures with a large angle (>60°), which is unfavorable for gas drainage. The expansion zone in the floor within 2‐40 m in the rear of the working face is characterized by high unloading degree of vertical stress and developed fractures. Moreover, fractures with a small angle (<60°) dominate the spatial distribution of the fractures, which is favorable for gas drainage. The research results can not only be a beneficial supplement to the theory of coal and gas co‐exploitation in multi‐seam mining but also provide theoretical support for optimizing the design parameters of cross‐measure boreholes under similar conditions. Abstract : By utilizing bonded block model‐distinct element modeling (BBM‐DEM) detailed simulation method, this research performed zonal statistics and comparative analysis on distribution laws of fractures of coal and rock in the floor under mining and obtained distribution laws of fractures in floor strata of the coal seam under the influence of mining the coal seam group with close distance.